Atividade antinociceptiva e avaliação histomorfológica da fotobiomodulação laser na articulação temporomandibular de ratos - Barretto, Sandra Regina (2013)
Temporomandibular Disorder (TMD) is a dysfunction that affects the temporomandibular joint (TMJ), characterized primarily by the presence of pain. It has been shown that low level laser therapy (LLLT) presents analgesic and anti-inflammatory effects in cases of TMD, but still experimental studies are scarce in order to understand the mechanisms involved in this biological activity. Therefore, the purpose of this work was to evaluate the ability of LLLT to control pain and inflammation induced by different chemical agents injected in the rat s TMJ. A study was carried out in two steps. At first induction of nociception was performed with 2.5% formalin in 25 Wistar rats ATM of 25 (300 ± 50 g), which they were randomly divided into 05 groups (n=5): CRG (no treatment); DFN (diclofenac sodium); LST1 (LLLT 12,5 J/cm2); LST2 (LLLT 52.5 J/cm2) and LST3 (LLLT 87.5 J/cm2). The LLLT was performed in a single application, with the apparatus laser with 780 nm (GaAlAs diode laser). The animals were evaluated considering the nociceptive behaviors characterized by rubbing the orofacial (RO) region and flinching the head (FH) quickly, analyzed separately and summed the behaviors. Data were analyzed through Anova test (one way) and Tukey s test. In the second stage, inflammation was induced in the TMJ of 45 Wistar rats (300 ± 50 g) with carrageenan to 1%. Then, the animals were divided into 03 main groups (n=15): CRG (no treatment); DFN (diclofenac sodium) and LST3 (LLLT 52.5 J/cm2). The LLLT was performed every 48 h, with the laser device described above. At specific times (24 h, 3 days and 7 days) five animals from each group were randomly sacrificed and their TMJ specimens were processed and stained with hematoxylin/eosyn (HE). The data were submitted to descriptive analysis regarding to semiquantitative and morphostrutural changes and mphasizing the inflammatory aspects and vascular neoformation. Data were analyzed through Kruskal-Wallis test and Dunn s post-hoc test. The results showed that DFN, LST2 and LST3 significantly reduced nociceptive responses characterized by the sum of the behaviors of FH and RO (p<0.001). DFN was also able to reduce the behaviors of FH (p< 0.05) and CO (p< 0.01) when assessed separately, as well as it was observed in LST2 (FH and RO, p<0.001). The LST1 did not elicit nociceptive effect. In the histological analysis, an inflammatory infiltration was observed significantly more intense in CRG than in DFN and LST2 in 24 h (P<0.05 e p<0.001), 3 days (p<0.01 e p<0.001) and 7 days (p<0.001 e p<0.01). In addition, the contingent of neutrophils was more conspicuous in CRG than in other groups in 24h. The vascular neoformation was less expressive in CRG than DFN (p<0.001) and LST2 (p<0.001) in 24 h, while in 3 days, exhibited greater quantitative LST2 blood vessels than CRG (p<0.001) and DFN (p<0.001). In 7 days, there was no difference in vascular content between experimental groups (p>0.05). Based on the results, one might conclude that the LLLT showed anti-inflammatory and antinociceptive effect in the inflammation induced in the TMJ of animals.